2015
DOI: 10.1590/1807-3107bor-2015.vol29.0133
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and social factors: impact on quality of life in Brazilian children

Abstract: The objective of this study was to evaluate the impact of dental caries and social determinants in the Oral Health Related Quality of Life (OHRQoL) of children in Belo Horizonte, Brazil. This is a population-based cross-sectional study with a representative sample of 1,204 children aged 8 to 10 years randomly selected from 19 public and private schools. The children were clinically examined at school by two trained and calibrated examiners (Kappa = 0.78 -1.00). The Decayed, Missing and Filled Teeth Index (DMF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
(33 reference statements)
3
32
0
10
Order By: Relevance
“…In Brazil, children attending public schools generally present a lower socioeconomic status (SES). 21,33,34 Moreover, low SES is closely associated with a worse psychological and cognitive functioning, 35 which in turn could affect the children's understanding of the questionnaires. Previous studies have revealed that socioeconomic factors exert a direct influence on answers regarding the impact of adverse health conditions on quality of life.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, children attending public schools generally present a lower socioeconomic status (SES). 21,33,34 Moreover, low SES is closely associated with a worse psychological and cognitive functioning, 35 which in turn could affect the children's understanding of the questionnaires. Previous studies have revealed that socioeconomic factors exert a direct influence on answers regarding the impact of adverse health conditions on quality of life.…”
Section: 21mentioning
confidence: 99%
“…13,14,15,16,17,18,19 The prevalence of impact on OHRQoL observed in previous studies using this assessment tool has ranged from 29.5% to 94.8%, with the "oral symptoms" domain reported as the most negatively affected. 20, 21,22,23 The child-OIDP was developed by Gherunpong et al, 5 and translated and validated for the Brazilian population by Castro et al 14 This index evaluates the impact of oral health in the quality of life through eight daily activities (eating, speaking, mouth cleaning, sleeping, smiling, emotional status, studying, and social contact). Previous studies using child-OIDP have reported the prevalence of impact on OHRQoL ranging from 28.6% to 89.8%.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Dental caries can induce complications, such as pain, chewing discomfort, sleep difficulties, and aesthetic problems. [14][15][16] Moreover, dental caries can affect the child's education and growth 17 and has been shown to be associated with the need for child hospitalization. 18 Traditionally, dental caries is recorded at the level of dentin cavities in dental public health initiatives in schools.…”
Section: Introductionmentioning
confidence: 99%
“…O autocuidado desde os anos da infância implica em uma melhor saúde bucal na vida adulta e menor impacto bio-psicossocial (4) beliefs about oral health care (held by individuals and their parents . Somadas ao exame clínico, a avaliação da Qualidade de Vida Relacionada à Saúde Bucal (QVRSB) (5) e a avaliação da percepção estética (6) mensuram os impactos funcionais e psicossociais das doenças bucais, auxiliando os profissionais na compreensão integral do paciente.…”
Section: Introductionunclassified
“…Na avaliação da QVRSB, aspectos como o impacto funcional, os sintomas orais, o bem-estar social e o bem-estar emocional são avaliados (5) , e a literatura aponta uma forte associação da presença da cárie dentária com impactos na qualidade de vida em crianças (6,7) , principalmente na presença de lesões de cárie não tratadas (4) beliefs about oral health care (held by individuals and their parents e em situação de vulnerabilidade social (7,8) .…”
Section: Introductionunclassified